Investigação do efeito de injeção de líquido por orifícios múltiplos na formação de gotas em um lavador Venturi - Guerra, Vádila Giovana (2009)
Venturi scrubbers are widely used in industrial plants in the cleaning of gases. In these scrubbers, the cleaning elements are the droplets formed at the injection of a liquid in the gas containing pollutants. The droplets act as collectors, incorporating the element to be removed. The liquid is usually injected through several orifices that promote a distribution of the droplets in the gas duct. The number of experimental studies in the formation of droplets in the Venturi scrubber is scarce, especially those concerned with the variation of the droplet size with the number of orifices of liquid injection. Therefore, the present work focused on the experimental investigation of the effects of the liquid injection in multiple jets in the formation and distribution of droplets in a Venturi scrubber. A laboratory scale scrubber, with a throat of 27 by 40 mm of cross-sectional, horizontally placed, was investigated. The data on droplet size was obtained with the Malvern Spraytec analyser, that makes possible in situ measurements by the passing a laser beam through the throat of the scrubber. The droplet size was analyzed varying the number of orifices of injection of the liquid from 1 to 4, the liquid flow rate between 300 and 1200 mL/min and the gas velocity in the throat of 59, 64, 69 and 74 m/s (L/G between 0.07 and 0.3 L/m3). The axial positions for measurements along the scrubber were varied between 120 and 240 mm. The effect of the formation of liquid film in scrubber walls was also analyzed. The experimental results showed that the increase of the liquid flow rate allowed a better distribution of the liquid inside the throat and also caused a stronger interaction among the jets. The number of injection orifices showed significant influence in the measured droplet size inside the throat, with the increase of the drop size with the increase of the number of orifices in operation. The interaction between jets and their droplets showed to have influence in the final size of the measured drop, since these sizes were larger in jets with larger interactions. The increases in the liquid jet and in the gas velocities favored the atomization process, causing decrease in the droplet sizes. The fraction of liquid film deposited in the walls of the scrubber varied significantly with the number of orifices in operation and consequently with the different penetrations of the jets. In general, jets with excessive penetrations generated a larger film fraction deposited in the walls of the scrubber and a smaller size of droplets. Through the analysis of dimensionless parameters, it was possible to quantify the influence of each operational condition in the size of the droplets generated inside of the studied Venturi scrubber.